Microbiological study of fish from the rural market of Katana on the edge of Kahuzi-Biega National Park, South Kivu Province, DRC - Bunani, Lushombo; MINZANGI, KAZADI; Kanimba, Kabongo; Tshiamala, Ololo; Bokungu, Efoloko; Kayeye, Bahizire; Badesire, Valery Byenda; olivier, Zigashane; Muhindo, Mutabazi (Orapuh Journal, 2025)
IntroductionSafeguarding public health requires effective planning and adequate epidemiological surveillance. Microbial foodborne illnesses are a major public health problem.Purpose This study aims to assess bacterial infestation in fish sold at the rural market of Katana, located on the edge of the Kahuzi-Biega National Park in South Kivu Province, Democratic Republic of the Congo.Methods Fish samples were collected, and bacterial cultures were performed on culture media. Identification was conducted using Gram staining at the Bacteriology Laboratory of the Fomulac/Katana General Reference Hospital in Katana, located in Kabare Territory, north of Bukavu City. For morphological identification, each sample was analysed in triplicate. Data were statistically analysed using the F test and the χ² test with Past version 4.10 software.Results Rod-shaped bacteria accounted for 52.6% of isolates, of which 93.3% were Gram-negative and 6.6% were Gram-positive. Among the Gram-negative bacteria, 21.4% were identified as Vibrio cholerae, while 71.9% were classified as other bacteria. Gram-positive bacteria were observed in species of Haplochromis sp. and Limnotrissa miodon. Gram-negative diplococci comprised 95.4% of isolates, compared to 4.5% that were Gram-positive. Among cocci, Gram-positive cocci accounted for 60%, while Gram-negative cocci made up 40%. The Hikojima strain of Vibrio cholerae was detected in 100% of Vibrio cholerae colonies. Biochemical identification revealed the presence of Vibrio cholerae, Citrobacter sp., Enterobacter sp., Salmonella sp., Escherichia coli, and Klebsiella sp. Statistical analysis showed no significant difference between fish species and the bacteria sought or between fish species and fish condition. However, there was a significant difference between colony characteristics and both the culture medium and fish condition, while no significant difference was observed between the culture medium and the bacteria sought.ConclusionFish sold at Katana's rural market are contaminated with bacteria regardless of the conditioning methods used. The unsanitary conditions of the market, display cases, and vendors' hygiene practices are the primary sources of contamination.